Prolonged Nasoenteral Tube Feeding in Children Contradicts Best Practice Guidelines. (1st June 2016) - Turner, J; Abobo, M; Blatz, D; Hartfield, D; Mager, D
Abstract: BACKGROUND: Expert consensus guidelines from the Canadian Pediatric Society and the American Academy of Pediatrics state that naso-enteral tube feeding is not appropriate for long term home nutrition support. Therefore, gastrostomy tubes are recommended for nutrition support predicted to last 2-3 months or more. A 2010 survey of pediatric health care providers at our institution demonstrated that 73% were unaware of these guidelines and 47% would consider a G tube only after 3-6 months. OBJECTIVES: The objective of this study is to determine whether the duration of nasoenteral tube feeding in children at our centre is consistent with expert consensus guidelines. DESIGN/METHODS: Prospectivechart review of all patients younger than 17 years of age referred for home nutrition support from January 2014 - July 2015 was conducted, with data collection until the present. RESULTS: 310 children were referred for nutrition support. Excluding patients out of province, lost to follow-up or deceased within a year from referral, 237 children were included. 88% were initially fed with a nasoen-teral tube; 76% of them were predicted to require tube feeding for months to years. 70% were fed with a nasoenteral tube for more than 3 months, with a mean duration of 4.8 months (range 0.07-20.3 months). 10% eventually underwent gastrostomy tube insertion, with a mean time to insertion of 9.7 months (0.07-20.3 months). CONCLUSION: The duration of nasoenteral tube feeding in a significant proportion of children is longer than recommended by expert consensus guidelines. An important contributing factor is lack of knowledge amongst pediatric health care practitioners about existing best practice guidelines.